The Use of Quizizz Application–Based Learning Media to Improve Vocabulary Mastery in Arabic Language Learning - Pebriansyah, Yayan; Syahid, Akhmad; Wahab, Abdul; Ansar (Journal of Digital Arabic Language Education, 2025)
The low level of students’ mastery of mufrodat (vocabulary) in Arabic language learning is one of the factors hindering the achievement of learning objectives, particularly among Grade VII students at MTsN 2 Makassar. Conventional teaching methods have resulted in students being less active and less motivated to participate in the learning process. Therefore, this study aims to examine the implementation of the Quizizz application–based learning media in teaching mufrodat in Arabic language learning and to analyze its effectiveness in improving vocabulary mastery among Grade VII students of MTsN 2 Makassar. This research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which consists of four stages: planning, action implementation, observation, and reflection. The study was conducted in two cycles with 38 Grade VII students of MTsN 2 Makassar as the research subjects. Data were collected through observation, tests (pre-test and post-test), and documentation. Data analysis was carried out using qualitative and quantitative approaches with comparative descriptive statistics. The results of the study indicate that the use of the Quizizz application–based learning media can increase students’ activeness and learning outcomes in mufrodat mastery. This is evidenced by improvements in learning completeness, which increased from 5.26% in the pre-cycle stage to 52.63% in Cycle I and 86.84% in Cycle II. Thus, the Quizizz application–based learning media is proven to be effective and feasible for improving mufrodat mastery in Arabic language learning.